Chemical composition of the renewed fire extinguishing powder and its physical characteristics - T, Azzaya; G, Burmaa; S, Alen; V, Batsaikhan (Bulletin of the Institute of Chemistry and Chemical Technology, 2020)
Water, foam, dry powder, carbon dioxide and liquid chemicals are used as fire extinguishers depending on the fire types. The fire classification of ABC type includes fires caused by paper, wood, dye, fuel, oil, lubricants and flammable gases. In this work, the investigation of the procedure for re-determining the composition of prepared fire extinguishers was carried out depending on the ratio of organic and inorganic substances, and their fire extinguishing activity was tested. The Sample-1 contains about 50% of ammonium dihydrophosphate (NH4H2PO4) which is taking into account the main component and the sum of ammonium sulphate (NH4)2SO4 and other inorganic and organic components by 50%. As a result of fire extinction tests, its fire extinguishing activity was higher than that of other Samples included different ratios of substances. Based on the thermogravimetric analysis of the Sample -1, the polymerization and water release process of NH4H2PO4 was detected as endothermic effect. The weight loss was occurred by 74% and 26% remained as P2O5 when temperature reached to highest degree. Some physical parameters such as moisture content, water repellence, density and particle size were analyzed according to ISO standard method and all these important parameters showed that it can meet the requirements for fire extinguishing powder standards. Гал унтраагч шинэчилсэн бэлдмэлийн найрлага, түүний физик шинж чанарын судалгаа Хураангуй: Ус, хөөс, хуурай нунтаг, нүүрс хүчлийн хий ба химийн шингэн бодис зэргийг галын төрлөөс хамааруулан гал унтраагчаар ашигладаг. Галын ABC ангилалд цаас, мод, будаг, шатахуун, тос, тосолгооны материал, шатамхай хий зэргээс үүдэлтэй гал хамаарна. Энэхүү ажлаар импортын гал унтраагч бодисын найрлагыг шинэчлэн тогтоох судалгааг органик ба органик бус химийн бодисуудын харьцаанаас хамааруулан явуулж, тэдгээрийн гал унтраах идэвхийг ABC ангиллын галд туршив. Үндсэн бүрдэл болох аммонийн дигидрофосфат (NH4H2PO4)-ыг 50%, (NH4)2SO4 ба бусад бүрэлдэхүүн бодисуудын нийлбэрийг мөн 50%-иар тооцоолон авсан. Бэлдмэл 1-ийн гал унтраах идэвх нь бусад бэлдмэлүүдийн идэвхээс өндөр байв. Бэлдмэлийн термографийн судалгаагаар NH4H2PO4-ын их хэмжээний дулаан шингээн полимержих, ус ялгаруулах процесс DTA-ийн муруйд эндо эффект хэлбэрээр илэрсэн ба температурын дээд утгад жингийн алдагдал 74%-д хүрч, 26% нь P2O5 хэлбэрээр үлдсэн. Гал унтраагч нунтгийн физик шинж чанарын гол үзүүлэлтүүд болох чийг, хувийн жин, ус үл нэвтрүүлэх чадвар, ширхэглэлийн хэмжээг тодорхойлсон ба эдгээр үзүүлэлтүүд нь стандартын шаардлагуудыг хангасан байна. Түлхүүр үг: Гал унтраагч нунтаг, идэвх, аммонийн дигидрофосфат, DTA/TG, физик үзүүлэлт